Enhanced performance of lipase-catalyzed kinetic resolution of secondary alcohols in monoether-functionalized ionic liquids - Zhou, Hancheng; Chen, Jin; Ye, Linmin; Lin, Haiqiang; Yuan, Youzhu; 袁友珠 (Bioresource Technology, 2011)
Several cationic monoether-functionalized ionic liquids (MEF-ILs) with different substituents were synthesized and used as media for kinetic resolution of secondary alcohols catalyzed by several lipases. The results indicate that Novozym 435 (an immobilized Candida antarctica Lipase B) had higher efficiency compared to other lipases in deracemization. The alkyl substituents at the 2- and 3-positions in the imidazolium ring of MEF-ILs were found to contribute to the increased enantioselectivity and enhancement of the reaction rate, respectively, while the higher stereo-hindrance of ether bonds decreased the activity. An enantioselectivity higher than 99% with 50% conversion of rac-1-phenylethanol was achieved using the catalyst system comprised of Novozym 435 and the MEF-IL 1-(3-ethoxypropyl)-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide. The catalytic system could be separated and reused without considerable activity loss. MEF-ILs can be a new class of enzyme-benign media suitable for lipase-catalyzed kinetic resolution of secondary alcohols. (C) 2011 Elsevier Ltd. All rights reserved. National Natural Science Foundation of China[20873108, 20923004]; NFFTBS[J1030415]; National Basic Research Program of China[2011CBA00508]